Design, Synthesis, In Vitro, and In Silico Studies of New N5-Substituted-pyrazolo[3,4-d]pyrimidinone Derivatives as Anticancer CDK2 Inhibitors - Waheed A. Zaki; Selwan M. El-Sayed; Mohamed Alswah; Ahmed El-Morsy; Ashraf H. Bayoumi; Abrahman S. Mayhoub; Walaa H. Moustafa; Aeshah A. Awaji; Eun Joo Roh; Ahmed H.E. Hassan; Kazem Mahmoud (MDPI AG, 2023)
CDK2 is a key player in cell cycle processes. It has a crucial role in the progression of various cancers. Hepatocellular carcinoma (HCC) and colorectal cancer (CRC) are two common cancers that affect humans worldwide. The available therapeutic options suffer from many drawbacks including high toxicity and decreased specificity. Therefore, there is a need for more effective and safer therapeutic agents. A series of new pyrazolo[3,4-d]pyrimidine analogs was designed, synthesized, and evaluated as anticancer agents against the CRC and HCC cells, HCT116, and HepG2, respectively. Pyrazolo[3,4-d]pyrimidinone derivatives bearing N5-2-(4-halophenyl) acetamide substituents were identified as the most potent amongst evaluated compounds. Further evaluation of CDK2 kinase inhibition of two potential cytotoxic compounds 4a and 4b confirmed their CDK2 inhibitory activity. Compound 4a was more potent than the reference roscovitine regarding the CDK2 inhibitory activity (IC50 values: 0.21 and 0.25 µM, respectively). In silico molecular docking provided insights into the molecular interactions of compounds 4a and 4b with important amino acids within the ATP-binding site of CDK2 (Ile10, Leu83, and Leu134). Overall, compounds 4a and 4b were identified as interesting CDK2 inhibitors eliciting antiproliferative activity against the CRC and HCC cells, HCT116 and HepG2, respectively, for future further investigations and development.